Peran Kepala Sekolah SMK Negeri 1 Dolok Sanggul dalam Pelaksanaan Manajemen Berbasis Sekolah dan Hubungannya dalam Kepemimpinan Pendidikan Kristen - Ningsih Pandiangan; Samuel Nababan; Christian Rosen Sitorus; Maris Simbolon; Radot Manalu (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The role of the principal of SMK Negeri 1 Dolok Sanggul in implementing school based management in the context of its relationship with Christian educational leadership in order to be able to improve the quality of the learning process in the school context. Therefore, this paper aims to describe the role of school principals in implementing SBM and this research uses qualitative researches were interviews, observation, and qeustionnaiers. The result of the research are the influence of the role of the school principal on the implementasion of school based management and its relationship in Christian educational leadership. Keywords:Headmaster, School Based Management, Christian Education